An Acceptor–Donor–Acceptor Structured Small Molecule for Effective NIR Triggered Dual Phototherapy of Cancer. (24th February 2020) - He, Zheng; Zhao, Linlin; Zhang, Qiang; Chang, Meijia; Li, Chenxi; Zhang, Hesheng; Lu, Yan; Chen, Yongsheng
Abstract: Dual phototherapy, including photodynamic therapy (PDT) and photothermal therapy (PTT), is regarded as a more effective method for cancer treatment than single PDT or PTT. However, development of single component and near‐infrared (NIR) triggered agents for efficient dual phototherapy remains a challenge. Herein, a simple strategy to develop dual‐functional small‐molecules‐based photosensitizers for combined PDT and PTT treatment is proposed through: 1) finely modulating HOMO–LUMO energy levels to regulate the intersystem crossing (ISC) process for effective singlet oxygen ( 1 O2 ) generation for PDT; 2) effectively inhibiting fluorescence via strong intramolecular charge transfer (ICT) to maximize the conversion of photo energy to heat for PTT or ISC process for PDT. An acceptor–donor–acceptor (A‐D‐A) structured small molecule (CPDT) is designed and synthesized. The biocompatible nanoparticles, FA‐CNPs, prepared by encapsulating CPDT directly with a folate functionalized amphipathic copolymer, present strong NIR absorption, robust photostability, cancer cell targeting, high photothermal conversion efficiency as well as efficient 1 O2 generation under single 808 nm laser irradiation. Furthermore, synergistic PDT and PTT effects of FA‐CNPs in vivo are demonstrated by significant inhibition of tumor growth. The proposed strategy may provide a new approach to reasonably design and develop safe and efficient photosensitizers for dual phototherapy against cancer. Abstract : A simple yet general strategy is proposed to develop sensitizing agents for effective near‐infrared‐triggered dual phototherapy of cancer based on an acceptor–donor–acceptor structured small molecules. The biocompatible nanoparticles, FA‐CNPs, present high photothermal conversion efficiency (PCE = 36.5%) and efficient 1 O2 generation capacity ( Φ = 18.6%) under single 808 nm laser irradiation.